2020
DOI: 10.1161/circresaha.120.316857
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Integrin α5 to Annexin A2 by Flow Drives Endothelial Activation

Abstract: Rationale: Atherosclerosis preferentially occurs at specific sites of the vasculature where endothelial cells (ECs) are exposed to disturbed blood flow. Translocation of integrin α5 to lipid rafts promotes integrin activation and ligation, which is critical for oscillatory shear stress (OSS)-induced EC activation. However, the underlying mechanism of OSS promoted integrin α5 lipid raft translocation has remained largely unknown. Objective: The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 51 publications
1
55
0
1
Order By: Relevance
“…Mechano-homeostasis plays a key role in maintaining the biological functions of the cardiovascular system and the pathological development of cardiovascular disease (Chien, 2007;Haga et al, 2007). A variety of mechanical stresses change, coordinate and control a variety of vascular cells, including ECs and vascular smooth muscle cells (VSMCs) (Tanaka et al, 2019;Zhang et al, 2020;Ngai et al, 2020). Therefore, exploring the changes in the mechanical stress that arterial cells are subjected to is crucial to understanding the mechanobiological mechanisms underlying vascular cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Mechano-homeostasis plays a key role in maintaining the biological functions of the cardiovascular system and the pathological development of cardiovascular disease (Chien, 2007;Haga et al, 2007). A variety of mechanical stresses change, coordinate and control a variety of vascular cells, including ECs and vascular smooth muscle cells (VSMCs) (Tanaka et al, 2019;Zhang et al, 2020;Ngai et al, 2020). Therefore, exploring the changes in the mechanical stress that arterial cells are subjected to is crucial to understanding the mechanobiological mechanisms underlying vascular cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study showed that mechanical stress on endothelial cells may lead to atherosclerosis through an interaction between intracellular A2 and integrin α5. Disturbed flood flow with oscillatory stress on endothelial cells accelerated the dephosphorylation of A2, which facilitated the binding of integrin α5 to the C-terminal domain of A2, thereby activating integrin α5β1, and leading to the progression of atherosclerosis [37,38]. Mechanisms of A2-mediated hemostasis and vascular homeostasis are summarized in Figure 1.…”
Section: A2 In Hemostasis and Vascular Homeostasismentioning
confidence: 99%
“…Clustering of ganglioside-enriched lipid rafts regulate the activity of integrin β1 [ 119 ]. Further, integrin α5 was found to be the protein most elevated from lipid rafts of endothelial cells that was exposed to oscillatory shear stress, which also increased the level of activated integrin α5 regulated by membrane cholesterol and fluidity [ 120 , 121 ]. Lipid raft molecules dissociate upon cholesterol removal [ 122 ].…”
Section: Integrin-glycosphingolipids Interactionsmentioning
confidence: 99%